Current Trends for Improving Safety of Stereotactic Brain Biopsies: Advanced Optical Methods for Vessel Avoidance and Tumor Detection - Akshulakov, Serik K.; Kerimbayev, Talgat T.; Biryuchkov, Michael Y.; Urunbayev, Yermek A.; Farhadi, Dara S.; Byvaltsev, Vadim A. (Frontiers in Oncology, 2019)
Stereotactic brain needle biopsies are indicated for deep-seated or multiple brain lesions and for patients with poor prognosis in whom the risks of resection outweigh the potential outcome benefits. The main goal of such procedures is not to improve the resection extent but to safely acquire viable tissue representative of the lesion for further comprehensive histological, immunohistochemical, and molecular analyses. Herein, we review advanced optical techniques for improvement of safety and efficacy of stereotactic needle biopsy procedures. These technologies are aimed at three main areas of improvement: (1) avoidance of vessel injury, (2) guidance for biopsy acquisition of the viable diagnostic tissue, and (3) methods for rapid intraoperative assessment of stereotactic biopsy specimens. The recent technological developments in stereotactic biopsy probe design include the incorporation of fluorescence imaging, spectroscopy, and label-free imaging techniques. The future advancements of stereotactic biopsy procedures in neuro-oncology include the incorporation of optical probes for real-time vessel detection along and around the biopsy needle trajectory and in vivo confirmation of the diagnostic tumor tissue prior to sample acquisition.